Efeito de bloqueadores meióticos na maturação e ultraestrutura de oócitos e sua conseqüência na produção de embriões in vitro - Sandri, Luciano Ricardo (2007)
The aim of this study was test the effect of Cordicepim (CY), an inhibitor of mRNA translation, associate with growth factor (IGF-I), in the presence or absence of Roscovitina (Ros), a mitogen promoting factor blocker. Twelve hours in culture media with CY plus 18 or 24 hours of maturation resulted in an average of 80% of oocytes reaching metaphase II. The blastocyst yield after 12 hours culture media with CY plus 18 hours of maturation without inhibition (32.3%) was similar (P>0.05) to the control group (39.6%). A negative effect of Ros on blastocyst yield was observed when not associated to CY, (16.7% in Ros vs 49% in control group). When the concentration of Ros associated with CY was reduced, the blastocyst yield was lower (8.3%) compared with the control group (36.4%). Transmission electron microscopy evaluation showed characteristics like a mature oocyte but also some characteristics of immature oocyte after 12 hours of inhibition. In conclusion, the temporary exposure of bovine oocytes to CY associated with IGF-I during in vitro maturation allowed an increase in culture time with no effect on cytoplasm ultra-structure and blastocyst yield, associated or not with Roscovitina